2010
DOI: 10.1111/j.1445-5994.2009.02108.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term percutaneous endoscopic gastrostomy feeding in young adults with multiple disabilities

Abstract: Unlike other people with neurological deterioration, young adults with lifelong multiple disabilities may live for many years with PEG feeding. There is little gain in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…This perspective was particularly evident in the Netherlands [45], [52], [66] and Belgium [35], [36]. Similarly, for individuals with intellectual disabilities, some parents believed that a PEG tube would increase physical suffering and social stigma [39], [69]. Conversely, a smaller number of US and Canadian studies indicated that some clinicians believed starting artificial nutrition at the end of life could provide freedom from pain and discomfort, as feeding tubes were perceived to increase the ease of feeding and administering medicines [40], [76].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This perspective was particularly evident in the Netherlands [45], [52], [66] and Belgium [35], [36]. Similarly, for individuals with intellectual disabilities, some parents believed that a PEG tube would increase physical suffering and social stigma [39], [69]. Conversely, a smaller number of US and Canadian studies indicated that some clinicians believed starting artificial nutrition at the end of life could provide freedom from pain and discomfort, as feeding tubes were perceived to increase the ease of feeding and administering medicines [40], [76].…”
Section: Resultsmentioning
confidence: 99%
“…Nurses’ decisions to report observations were often based on a “ gut feeling ” that “ something was wrong ” [52]. Similarly for individuals with intellectual disabilities, mothers [37], [69] and care workers [39] brought changes to the attention of specialists. Conversely, for decisions concerning withdrawal, it was the lack of change in a patient’s condition that triggered the decision process [70][74].…”
Section: Resultsmentioning
confidence: 99%
“…Who and when to make this decision can be a problem and communicating it in a binding way to those who may become involved in further health care can be complex [50, 71, 140]. The existence of ACDs should ideally be on the electronic medical record as an “alert”.…”
Section: Resultsmentioning
confidence: 99%
“…They also comprise a wide range of ages [4, 11, 4955] and conditions such as cancer [3, 4, 19, 24, 25, 5662], terminal respiratory diseases [6366], cardiac failure [26, 67–70], profound intellectual and physical disability, and advanced dementia [1, 47, 50, 62, 71, 72]. These patients pose a challenge in the ED because the majority appear not to have access to palliative care options, in particular those with non-cancer conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As in other patient populations, the decision to insert a PEG tube in an elderly demented patient should always be made on an individual basis (National Collaborating Centre for Acute Care, 2006;Kurien et al, 2010;Rabeneck et al, 1997). In children and adults with intellectual disability/mental retardation, feeding via PEG has been shown to improve nutritional status and quality of life in certain patients (Loser et al, 2005;Mathus-Vliegen et al, 2001) but not others (Lee & MacPherson, 2010); no randomized studies have been performed.…”
Section: Indications For Percutaneous Endoscopic Gastrostomymentioning
confidence: 99%